2018
DOI: 10.1155/2018/5806179
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Insecticide Resistance to Pyrethroids and Bendiocarb in Anopheles funestus from Tsararano, Marovoay District, Madagascar

Abstract: Introduction In Madagascar, malaria control relies on the countrywide use of long lasting insecticide treated bed nets (LLINs) and on indoor residual spraying (IRS) in the central highland area as well as a small area on the eastern coast. We tested insecticide resistance mechanisms of Anopheles funestus from Tsararano, a malaria endemic village in the coastal health district of Marovoay. Methods Insecticide susceptibility bioassays were done in July 2017 on first-generation Anopheles funestus (F1) to assess (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Indeed, previous data from sentinel sites of the National Malaria Control Programme across the country showed low resistance of species of the An. gambiae complex to bendiocarb [6,7]; resistance of species of the complex to the carbamate class of insecticide has been reported elsewhere in Africa in many studies [10,13,40,41].…”
Section: Susceptibility To Carbamatesmentioning
confidence: 99%
“…Indeed, previous data from sentinel sites of the National Malaria Control Programme across the country showed low resistance of species of the An. gambiae complex to bendiocarb [6,7]; resistance of species of the complex to the carbamate class of insecticide has been reported elsewhere in Africa in many studies [10,13,40,41].…”
Section: Susceptibility To Carbamatesmentioning
confidence: 99%
“…aegypti and Cx. quinquefasciatus resistance to PBO-synergized insecticides, while resistant Anopheles also developed GST and A296S-RDL dieldrin resistance mechanisms [31,37,42,49,50,54]. In this study, we found that both P450 and COE enzyme activities in field Cx.…”
Section: Discussionmentioning
confidence: 56%
“…We should note that it is unlikely that African Anopheles mosquitoes were exposed to PBO or PBO-synergized insecticide products before large-scale rollout of PBO-LLINs. As discussed earlier, the reduced PBO-LLIN killing efficacy is likely due to multiple resistance mechanisms [49,50,53,54]; i.e., adding PBO to LLIN may not be enough to combat Anopheles mosquitoes' resistance to pyrethroids. This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gambiae and An. funestus was observed [37,38], emphasizing the importance of AChE as a crucial target for malaria vector control strategies.…”
Section: Metabolic Proteins As Insecticide Targetsmentioning
confidence: 99%